Clinical and economic impact of aliskiren in uncontrolled hypertensive patients - Degli Esposti, Ezio; Tomic, Radovan (Farmeconomia. Health Economics and Therapeutic Pathways, 2012)
BACKGROUND: the majority of hypertensive patients do not achieve adequate blood pressure (BP) control and thus remain at risk of cardio-cerebrovascular events. Aliskiren, a novel antihypertensive drug acting as direct renin inhibitor, was authorized in Italy for the treatment of hypertension in patients who remain uncontrolled and at risk despite the use of at least two antihypertensive drugs. It was subject to an AIFA web-based monitoring registry. Results of the registry show a decrease of 20.8/9.2 mmHg in systolic/diastolic BP, within 6 months, when aliskiren is added to current therapy. OBJECTIVE: to evaluate the clinical and economic impact of such BP reduction in terms of avoidable cardio-cerebrovascular events. METHODS: an Excel-based Markov model compared aliskiren plus current antihypertensive treatment to current antihypertensive treatment alone over a 5-year horizon. Patients’ baseline characteristics and BP-reduction were taken from the AIFA registry and literature. Using Wilson and Anderson risk equations, the model simulated patient’s transitions from Pre-Event to Post-Event and Death, calculating the number of those who experience an event. Unit costs were assigned to treatments, events and follow-up. Sensitivity analyses considered: efficacy variability and societal costs of events. RESULTS: 2.47% of patients treated with aliskiren added-on to their antihypertensive therapy were expected to avoid an event. As observed in the AIFA registry, 19.8% of patients remained treated only with aliskiren whereas others reduced the number of antihypertensive treatments, leading to a 38.6% reduction of monthly concomitant antihypertensive treatment cost. Considering events and follow-up cost reduction, the per-patient annual incremental cost of aliskiren is calculated at € 187 and generates 0.042 QALYs over 5 years. The ICER was € 22,062 per QALY (€ 16,845 to € 30,771 for an efficacy range of ± 25%). Considering societal costs ICER was € 20,094 per QALY. Conclusions: AIFA registry real-world data confirmed aliskiren’s efficacy in uncontrolled hypertensive patients. Together with reaching their BP goals, patients consumed less medication from other antihypertensive drug classes and are expected to avoid cardio-cerebrovascular events. The ICER remained within acceptable thresholds, confirming that aliskiren represents a good investment in terms of health benefit.